Caracterización de Sistemas de Producción Bovina intensiva en el Cantón Latacunga Provincia de Cotopaxi. - Guachi Guachi, Nelson Fabricio (2020)
The present investigation was carried out in the 10 rural parishes of the Cantón Latacunga, Province of Cotopaxi with the objective of evaluating the structural and functional characteristics of the bovine production systems. A survey application methodology was used, collecting information on functional aspects in the production unit; the same ones that were analyzed by comparative tables followed by a hierarchical classification analysis. Obtaining as a result 34 farms distributed in 7 parishes with a total production of 26,080 liters of milk per day with a minimum of 1,460 liters in Toacaso and a maximum of 9,350 in Guaytacama, 25 farms apply supplementary feeding and 9 without supplementary feeding, at the technological level the parish of Mulalo 5 use mechanical milking and 3 manual milking, Toacaso 2 of the 3 continue with manual milking, the 34 farms use artificial insemination and 2 embryo transfer. Concluding that in most farms they use reproductive biotechnology and continuous grazing before supplementary feeding.